An Industrial quality control study on Kimberly-Clark Philippines Inc. - Family Care Dept. - Abeto, Paul (College of Engineering, 2006)
The Statistical Quality Control Study is conducted on Kimberly-Clark Philippines, Inc. (KCPI), based in San Pedro, Laguna. The study is focused on the quality system regarding the tissue paper division. The main objective of this study is to evaluate the sampling plan currently being implemented in the division and determine the process capability of the production process used at present. The study is focused on three different grades of tissue paper, namely Ace, Ambros, and Joy Hi-Save Quanta. For each grade, nine variables (absorbent capacity, absorbency wet out time, as is basis weight, detaching strength, handle strength, MD tensile, roll firmness, sheet width, and sheet length) and three attributes (packaging, roll and sheet attributes) were assigned to be analyzed for study. The study made use of Statistical Quality Control techniques such as control charting, stability analysis, process capability analysis, and acceptance sampling to evaluate the current system and determine if the process is in control and capable of operating within specifications. After plotting the control charts for each characteristic of each product grade, out of control points were found and nonrandome patterns were identified. With the assurance of the company that the out of control points were due to assignable causes, the group discarded the out of control points and plotted the revised control charts. Analysis of the revised control charts showed that some exhibit unusual form. Further study showed that it may be due to the device used to get the data, the assumptions made by the company and the number of inspections performed. The process capability analysis on the three product grades shows that the process, in terms of the variable characteristics, is off-centered and performing below its capacity. Corrective action must be implemented to further improve the process. The as is basis weight and MD tensile variables have negative Cpk's which indicates that the process mean does not fall in the specification limits. These variable characteristics are intrinsic to the hard roll which means that the raw material is of low quality. For the lot size of 120,000 tissue rolls, the average number of rolls produced in an 8-hour shift, the recommended sampling plan is 500 tissue rolls for attributes and 25-100 tissue rolls, depending on the inspection level used, for variables. It is based on the MIL STD 105E, for attributes and MIL STD 414, for variables. For variables, the computed sample size for Inspection Level I, which is 25 tissue rolls, is similar to the current sampling plan used by the company which is 24 tissue rolls. On the other hand, the current sample size of 80 tissue rolls for every shift for attributes is much lower compared to the computed sample size of 500 tissue rolls. The recommended sample size would ensure that items in the lots are well-represented during the sentencing of the lots. Another recommendation is for the company to find a supplier that will strictly comply with quality requirements of the raw materials being used by the company. It was found in the process capability analysis that variable characteristics related to the quality of the raw material have the lowest capability of operating within specifications. It is also recommended that a more precise and accurate measuring device is to be used in testing the sheet length and sheet width to gain a better analysis of the data. The implementation involves the application of the recommended sampling plan for a one month trial period. If the recommended sampling plan is found acceptable after the trial period, hiring of additional quality engineers and inspectors is suggested.